Phytochemical screening on 105 Sabahan medicinal plants - Mashitah Mohd Yusoff (2002)
Phytochemical screening was carried out on one hundred and five (105) Sabahan medicinal plants. The chemical contents were found to follow the following distribution, alkaloids (54 %), anthraquinones (28 %), flavonoids (52 %), saponins (74 %) and tannins (46 %). K2 analysis showed that the relationship between chemical constituent and plant species at p = 0.05 is significant (p < 0.05).